EMERGENCY MANAGEMENT AND RESUSCITATION OF VICTIMS IN ENCLOSED-SPACE FIRE DISASTERS: A CASE SERIES OF 17 PATIENTS AT E HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Enclosed-space fires represent a dangerous medical disaster due to the combined injury mechanisms of carbon monoxide (CO) poisoning, thermal burns, and inhalation injury. Objectives: To describe the clinical and subclinical characteristics, injury classification, and treatment outcomes of victims involved in the fire on January 7, 2026, treated at E Hospital, with a specific focus on analyzing the role of early bronchoscopy. Methods: A cross-sectional descriptive study was conducted on 17 patients.The disaster response protocol included: triage classification, arterial blood gas analysis, HbCO quantification, and early flexible bronchoscopy. Results: The mean age was 22.9 ± 2.6 years; females accounted for 52.9%. Two patients (11.8%) presented with grade III-IV inhalation injuries requiring proactive endotracheal intubation. Notably, bronchoscopy detected soot deposits and airway edema in 82.4% of victims, even in those with initially stable clinical presentations. One patient was admitted in a fully alert state, yet bronchoscopy revealed a grade III injury, leading to successful prophylactic intubation. There was no mortality; all patients were discharged after 3–10 days. Conclusion: Enclosed-space fires are associated with a high incidence of occult inhalation injury. Early bronchoscopy serves as the gold standard for risk stratification and decision-making regarding proactive airway management.Keywords: Enclosed-space fire, CO poisoning, Inhalation injury, Bronchoscopy, E Hospital.
Keywords: Enclosed-space fire, CO poisoning, Inhalation injury, Bronchoscopy, E Hospital.